Biological characteristics of strain Paecilomyces variotii NV01 isolated in Đăk Lăk pepper soil - Thanh Binh, Chu; Thi Viet Ha, Bui; Tuyen, Ho; Phuong Nhue, Nguyen (VNU Journal of Science: Natural Sciences and Technology, 2017)
From 15 pepper soil samples in Daklak, based on chitinase, protease, amylase, and cellulase activities, strain NV01 was chosen for further research. Selected strains NV01 were studied for morphology, colonial color, nutritive influences to spore formation; It has been shown that the PDA environment is suitable for the growth of strain NV01. After 14 days of inoculation, this fungus sporulated 10 6 conidia x cm -1 . The strain is capable of producing some extracellular enzymes such as amylase, cellulase, chitinase, and protease. The sequence-based results ITS1F and ITS4 showed that the strains were highly similar (100%) to Paecilomyces variotii KF305752 and were assigned as Paecilomyces variotii NV01. In Vietnam, there is very little research into the this fungus, and databases of biological characteristics are still limited.